Getting diversity at work to work: What we know and what we still don't know. Issue 2 (15th April 2013) - Guillaume, Yves R. F.; Dawson, Jeremy F.; Woods, Steve A.; Sacramento, Claudia A.; West, Michael A.
<x xml:space="preserve">Abstract</x> Diversity has the potential to significantly benefit organizations by leading to positive work outcomes when diversity 'works'. Unfortunately, not only is our knowledge limited as to the necessary conditions and the mechanisms by which diversity affects individual, work performance and organizational outcomes, but we still know very little about which diversity management practices are most effective in promoting positive outcomes. We analyse the literature on diversity and its management, and describe how the seven papers included in this section advance our understanding of what organizations can do to get diversity at work to work. Our discussion points to the need for more research on how diversity at multiple levels affects work and organizational outcomes; the development of integrative theory which takes into account that diversity might not only engender separation and variety but also disparity; as well as to the need for more empirical attention to the climates or cultures that facilitate the positive effects of diversity on work and organizational outcomes. We suggest that future research should also identify those people management practices that are most powerful in the creation of a positive diversity climate, and the factors that moderate and underlie its effects on work and organizational outcomes. We conclude with proposals about how this might be achieved.